Unraveling Metabolite Provisioning to Offspring Through Parental Fluids: A Case Study of the Brazilian Guitarfish, Pseudobatos horkelii - Wosnick, Natascha; Leite, Renata Daldin; Giareta, Eloísa Pinheiro; Morick, Danny; Hauser-Davis, Rachel Ann (Frontiers in Physiology, 2022)
Elasmobranchs have a very distinct metabolism, and many aspects related to the energetic dynamics of these animals remain poorly investigated. The reproductive period is particularly vulnerable for viviparous species, as part of the energy reserves of the parental biomass is reallocated for gamete production and embryo development. In this context, this study aimed to characterize parental metabolite provisioning to the offspring (both sperm and developing embryos) of the Brazilian Guitarfish, Pseudobatos horkelii, through glucose, β-hydroxybutyrate, triglycerides, and total cholesterol determinations in the uterine liquid (UL) and serum of pregnant females and in the seminal fluid (SF) and serum of males during the copulation period. No significant difference was observed for the analyzed markers between the UL and SF. Except for triglycerides, higher in female serum samples, all other energy markers were present at similar concentrations in the serum of both females and males. When comparing female UL and serum, significant differences were observed for triglycerides and total cholesterol. No differences were observed between SF and serum in males. The results indicate that all markers are being made available to offspring, possibly complementary to the yolk in the case of maternal liquid, and as an additional source for sperm mobilization required during egg fertilization in the case of the paternal fluid. Correlations between the markers in the parental matrices were also noted, compatible with the metabolic pathways activated during energy mobilization in vertebrates. Moreover, distinct marker predominance patterns were also noted for both UL and SF. Energy mobilization characterization directed to offspring through parental fluids aids in unraveling metabolic dynamics during the reproduction stage while also providing support for stress physiology studies to evaluate the indirect effects of parental allostatic overload in both sperm and developing embryos. Finally, energy mobilization assessments of parental fluids may also help elucidate how internal fertilization and viviparity evolved in this very distinct taxonomic group.